PERANAN MEDIA KOMUNITAS DI TENGAH ARUS GLOBAL MEDIA DALAM PENGEMBANGAN MASYARAKAT - Usman Usman (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
Community media is principally based on population groups that are in a limited geographical space. The concept that underlies the existence of community media is the same as non-governmental organizations (NGOs) that carry out joint activities to empower their communities. The existence of community media is seen from the broadcasting law No. 32 of 2002 institutions established by certain communities, which are independent, and not commercial to serve the interests of their community. Community media are not established to seek profits or profits or are not part of a company that seeks profit. Community media is established to develop and advance the community in achieving prosperity, by implementing programs that include culture, education, and information that describes the identity of the nation. In community development, community media is the right tool, because in the process community media is not for the sake of propaganda for certain groups or groups. In reviewing the influence of community media as a support for community development, Jan Servaes, a European scholar stated that there are three models of communication and development (models of communication and development), which are the basic concepts in this research, namely: diffusion of innovation (Lerner and Schramm concepts), technological determinism (technology that solves problems), and depedency.